Sawdust-Based Concrete Composite-Filled Steel Tube Beams: An Experimental and Analytical Investigation - Saavedra-Flores, E; Avudaiappan-, S (Multidisciplinary Digital Publishing Institute (MDPI), 2023)
Incorporating waste byproducts into concrete is an innovative and promising way to minimize the environmental impact of waste material while maintaining and/or improving concrete’s mechanical characteristics and strength. The proper application of sawdust as a pozzolan in the building industry remains a significant challenge. Consequently, this study conducted an experimental evaluation of sawdust as a fill material. In particular, sawdust as a fine aggregate in concrete offers a realistic structural and economical possibility for the construction of lightweight structural systems. Failure under four-point loads was investigated for six concrete-filled steel tube (CFST) specimens. The results indicated that recycled lightweight concrete performed similarly to conventional concrete when used as a filler material in composite steel tube beams. The structural effects of sawdust substitution on ultimate load and initial stiffness were less substantial than the relative changes in the material properties, and the ultimate capacity of the tested samples decreased moderately as the substitution percentage of sawdust increased. Moreover, the maximum load capacity was observed to decrease by 6.43–30.71% for sawdust replacement levels between 5% and 45.1% across all tested samples. Additionally, when using lightweight concrete with 5% sawdust, the moment value of the CFST sample was reduced by 6.4%. Notably, the sawdust CFST samples exhibited a flexural behavior that was relatively comparable to that of the standard CFST samples. © 2023 by the authors.